Penerapan Konsep Adventure Tourism Menggunakan Business Prosess Modeling Nitation - Siti Zahra Salma; Wiranto Wiranto; Asmawati S (Universitas Nusa Cendana, 2022)
Smart tourism is a tourism platform that has the functionality to assist tourists in providing information on existing tourist destinations. One of the tourist destinations, especially in the area of ​​West Sulawesi. Therefore, the application of smart tourism in Majene district will certainly help tourists. However, tourist destinations in Majene do not necessarily have good access. As a result, many of the managers of tourist destinations with poor access prefer to go out of business due to the lack of tourists visiting. The purpose of this research is to design additional features in smart tourism, so that tourists can use the help of the existing community to more easily visit tourist destinations that are difficult to reach, which is called adventure tourism. The system development method used is the prototype method. The prototype method used includes the analysis, design, and implementation stages. The analysis stage performs problem analysis using the piece method and obtains comparison results that show the advantages of using the provided system and manual. The functional requirements analysis stage using use cases, data flow diagrams, entity relationship diagrams, and business process modeling notations creates a clearer process flow in development. The design stage produces additional menus in feature development. The implementation stage gives the results of the system display in the form of a final design adventure tourism features.